PENGEMBALIAN KERUGIAN KEUANGAN NEGARA BERDASARKAN REKOMENDASI BADAN PEMERIKSA KEUANGAN (BPK) HUBUNGAN DENGAN UNSUR KERUGIAN NEGARA DALAM TINDAK PIDANA KORUPSI - Paeh, Karel Antonius (Katalogis, 2017)
The research questions in the study were (1) how was the proofing of state financial loss based on Recommendation by the supreme audit agency in central sulawesi province? (2) what were the problems faced by the investigators in proofing the state financial loss based on Recommendation by the supreme audit agency in central sulawesi province? The objectives of the research were (1) to identify and analyze the state financial loss based on Recommendation by the supreme audit agency in central sulawesi province, and (2) to identify and analyze the problems faced by the investigators in proofing the state financial loss based on Recommendation by the supreme audit agency in central sulawesi province. It was juridical normative research. The results of the research showed that (1) the proofing of state financial loss was undertaken by the investigators â€“ prosecutors, by the assistance of auditors in the development finance controller (BPKP) in central sulawesi province to calculate the state financial loss in a crime, the problems concerned wth different perceptions among the investigator, prosecutors and BPKP auditors who persisted on their own scientific principles. Based on the research findings, it is recommended that (1) BPKP auditors in centralÂ sulawesi province be involved in the investigations as auditors in criminal cases in order that the investigators and prosecutors collect the results of the results of calculation of state financial loss more quickly, and (2) BPK auditors and BPKP auditors be exclusively positioned as professionals in their discipline to defend their auditing results, support other relevant experts in the line with the imposition of the laws in parallel with the inconsistencies against the prevailing law and state regulations.